PENGARUH KEPEMIMPINAN TERHADAP SEMANGAT KERJA GURU DI SMK TARUNA “X” PEKANBARU - yapentra, arhipen; Lamin, Lamin (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
The purpose of this study is to determine the Influence of Principal Leadership on Teacher Work Spirit at SMK Taruna “X” Pekanbaru. The population of this study consisted of 59 teacher respondents, while the sample was 58 respondents. The research method used in this study is Descriptive and Quantitative methods, followed by analysis using simple linear regression. The data processing results show that the average value of the Leadership variable is 4.03, meaning that respondents' answers for all Leadership statements are Agree (good). Based on the regression test results, it is known that the t_count > t_table (6.817 > 2.003) and significance < 0.05 (0.000 < 0.05), thus Ha is accepted. This means that leadership has a positive and significant effect on Work Spirit. The R-square value obtained is 0.454 or 45.4%, meaning that the leadership variable has an influence on the Work Spirit of SMK Taruna “X” Teachers by 45.4%, and the remaining (100 - 45.4) 54.6% is influenced by other variables not examined in this study